A rare case of acrodysostosis type 2 with PDE4D mutation in a young female: a case report - Muhammad Sheraz Hameed (22282597) (2025)
Acrodysostosis (ADO) is a rare form of peripheral dysostosis characterized by skeletal malformations, growth delays, short stature, and distinctive facial features caused by in part by underdeveloped (hypoplasia) of facial bones. Skeletal dysplasia is specific and includes disproportional short stature with short extremities and brachydactyly, multiple cone-shaped epiphyses, scoliosis or kyphosis with spinal stenosis, and advanced bone maturation. Herein, we are highlighting a case that presented with clinical features such as brachydactyly, delayed milestone, growth delay, muscle weakness and nasal hypoplasia. Patient genetic testing was in line with the diagnosis of acrodysostosis. The clinic-radiological correlation was also suggestive of the rare diagnosis of ADO. Other Information Published in: Oxford Medical Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/omcr/omae169